Development of efficient processing method for the production of cellulose nanofibrils from oil palm biomass - Noor Megashah, Liana (2021)
Cellulose nanofibrils (CNFs) is an emerging, versatile nanomaterial with vast applications such as plastics, papers, composites, thickener agents, healthcare, coatings etc. Nevertheless, there are several issues in the sustainable production of CNFs pertaining to the non-ecofriendly pretreatment method for cellulose isolation related to the use of chlorinated solution, as well as high energy intensity and throughput limitation which limit the productivity during nanofibrillation process by wet disc mill (WDM). The natural cellulose high degree of polymerization (DP) caused the formation of a highly viscous cellulose suspension during processing and was hypothesized to contribute to the high energy requirement and low productivity of the nanofibrillation process. In this research, cellulose isolation from oil palm biomass was conducted by using a totally chlorine free (TCF) bleaching for lignin removal. A multi-step pretreatment method consisting of a sequence of pretreatment, i.e., superheated steam (SHS), enzymatic hydrolysis and 5% NaOH was evaluated for its effectiveness in hemicellulose removal and its effect on the environmental loads. The multistep pretreatment method was compared with the conventional soda pulping method at 14% NaOH under elevated pressure. After cellulose isolation step, the cellulose was treated by SHS at 150°C for 1 and 2h (SHS1 and SHS2) aimed at depolymerization for DP reduction. This method was compared with the enzymatic hydrolysis. It was shown that the multi-step pretreatment method produced lesser purity cellulose from oil palm biomass (83-88%) as compared to soda pulping method (89-95%). Its environmental load based on qualitative analysis was however similar to that of soda pulping. The TCF bleaching successfully removed the lignin almost completely, showing the effectiveness of TCF bleaching as an alternative to chlorinated bleaching. In the subsequent experiment for cellulose DP reduction, it was demonstrated that SHS treatment caused cellulose DP reduction up to 43% after 2h of SHS treatment (SHS2). As a comparison, enzymatic hydrolysis contributed to almost similar percentage reduction after 6h and 12h of hydrolysis using 20 FPU/g and 10 FPU/g cellulase, respectively. The SHS treated cellulose was used in nanofibrillation process, and it was interesting to note that SHS2 cellulose (DP - 820) contributed to lower viscosity CNFs suspension (60 cP), shorter processing duration (4.0 h/kg), and smoother processing without clogging even at 4 wt% solid content processing; compared to the untreated (UT) cellulose (DP - 1,440). All these contributed to higher CNFs productivity by 86% from 0.044 kg/h to 0.320 kg/h, and lower energy consumption by 90% from 42.3 kWh/kg to 4.2 kWh/kg, compared to the untreated (UT) cellulose. The results obtained confirmed the hypothesis that CNFs productivity and energy consumption were related to the original characteristic of cellulose, i.e., high DP. The SHS treatment also contributed to versatile properties of CNFs produced, as exhibited by the characteristics of the CNFs as well as the CNF films. CNF-SHS films were thinner, stiffer and had smoother surface compared to CNF-UT film. Higher light transmittance by 22.5% and greater water-repellent property by 15.1% were also recorded for CNFSHS2 film as compared to the CNF-UT film. SHS treatment also promotes the production of versatile mechanical properties of CNF films, to meet vast applications of nanofilms. Feasibility analysis conducted showed that the pretreatment and production methods proposed are technical feasible, which can attribute to the lower environmental loads compared to the conventional process, the simplicity of the process, as well as the availability of the steam energy should the plant be located near the palm oil mill. It is also economically feasible with the NPV of USD 714,031 for 10 years and IRR of 45%. CNFs from OPEFB is also potentially marketable based on its comparable characteristics to those of commercial CNFs, as well as its market acceptability based on the survey. Overall, the proposed processing methods provided herewith will contribute significantly towards a more sustainable CNFs production from oil palm biomass in the near future.